YOUTH IN THE DIGITAL AGE AND REPRODUCTIVE HEALTH PROBLEMS - Atok, Yosefa Sarlince; Vilastry Nuhan, Maria; E. M. Sormin, Roslin (LPPM Univ. Ibn Khaldun Bogor, 2022)
It is important to do health education to cultivate healthy behaviors, much better done during childhood than trying to change these behaviors in adulthood. In this digital era, technological developments are increasing rapidly. The more advanced technology is also increasingly encouraging an individual to be increasingly apathetic to the circumstances of the people around him, including teenagers. Community service aims to educate teenagers in stemming information that can damage teenagers' personalities and be ready to face advances in information technology that is developing very quickly. This community service activity was carried out at GMIT Oeboboa, which is located at, Manusak Village, East Kupang District, Kupang Regency. This activity was carried out in April 2022. The targets and partners in this activity were GMIT Oeboboa Youth, Lecturers, and Students of the Midwifery Study Program STIKes Maranatha Kupang.